Ectonucleotidases in Solid Organ and Allogeneic Hematopoietic Cell Transplantation. (16th October 2012) - Chernogorova, Petya; Zeiser, Robert
Abstract : Extracellular nucleotides are ubiquitous signalling molecules which modulate distinct physiological and pathological processes. Nucleotide concentrations in the extracellular space are strictly regulated by cell surface enzymes, called ectonucleotidases, which hydrolyze nucleotides to the respective nucleosides. Recent studies suggest that ectonucleotidases play a significant role in inflammation by adjusting the balance between ATP, a widely distributed proinflammatory danger signal, and the anti-inflammatory mediator adenosine. There is increasing evidence for a central role of adenosine in alloantigen-mediated diseases such as solid organ graft rejection and acute graft-versus-host disease (GvHD). Solid organ and hematopoietic cell transplantation are established treatment modalities for a broad spectrum of benign and malignant diseases. Immunological complications based on the recognition of nonself-antigens between donor and recipient like transplant rejection and GvHD are still major challenges which limit the long-term success of transplantation. Studies in the past two decades indicate that purinergic signalling influences the severity of alloimmune responses. This paper focuses on the impact of ectonucleotidases, in particular, NTPDase1/CD39 and ecto-5′-nucleotidase/CD73, on allograft rejection, acute GvHD, and graft-versus-leukemia effect, and on possible clinical implications for the modulation of purinergic signalling after transplantation.